Impact of age on treatment response in men with prostate cancer treated with radiotherapy. Issue 3 (27th December 2021) - Bryant, Alex K.; Nelson, Tyler J.; McKay, Rana R.; Kader, A. Karim; Parsons, J. Kellogg; Einck, John P.; Kane, Christopher J.; Sandhu, Ajay P.; Mundt, Arno J.; Murphy, James D.; Rose, Brent S.
Abstract: Objective: To analyse the effect of age at diagnosis on clinical outcomes of localized prostate cancer (PCa) treated with radiation therapy. Subjects and methods: We identified 12 784 patients with intermediate‐ or high‐risk localized PCa treated with radiation therapy (RT) and neoadjuvant androgen deprivation therapy (ADT) between 2000 and 2015 from nationwide Veterans Affairs data. Patients were grouped into three age categories (≤59, 60–69, and ≥70 years old). Outcomes included immediate PSA response (3‐month post‐RT PSA and 2‐year PSA nadir, grouped into <0.10 ng/ml, 0.10–0.49 ng/ml, and ≥0.50 ng/ml), biochemical recurrence, and PCa‐specific mortality. Multivariable regression models included ordinal logistic regression for short‐term PSA outcomes, Cox regression for biochemical recurrence, and Fine‐Gray competing risks regression for PCa‐specific mortality. Results: A total of 2136 patients (17%) were ≤59 years old at diagnosis, 6107 (48%) were 60–69 years old, and 4541 (36%) were ≥70 years old. Median follow‐up was 6.3 years. Younger age was associated with greater odds of higher 3‐month PSA group (≤59 vs. ≥70: adjusted odds ratio [aOR] 1.90, 95% CI 1.64–2.20; p  < 0.001) and higher 2‐year PSA nadir group (≤59 vs. ≥70: aOR 1.89, 95% CI 1.62–2.19, p  < 0.001). Younger age was associated with greater risk of biochemical recurrence (≤59 vs. ≥70: adjusted hazard ratio 1.45, 95% CI 1.26–1.67, p  < 0.001) but not PCa‐specific mortality ( p  = 0.16). Conclusion: In a large nationwide sample of US veterans treated with ADT and RT for localized PCa, younger age was associated with inferior short‐term PSA response and higher risk of biochemical recurrence.